2009
DOI: 10.1093/fampra/cmp023
|View full text |Cite
|
Sign up to set email alerts
|

What can family physicians contribute in palliative home care in Taiwan?

Abstract: Through palliative home care with the participation of family physicians, patients' preference could be a significant determinant of home death. Our finding can be helpful to the establishment of an ethical care model for terminal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Involving family physicians for caring patients at home, in liaison with the palliative home care team, can be helpful in establishing an ethical care model in terminal cancer patients. [ 25 ] OOH is an integral part of our care process; provided in liaison with the LGP. In our study, 421 (83.20%) patients had access to the LGP.…”
Section: Discussionmentioning
confidence: 99%
“…Involving family physicians for caring patients at home, in liaison with the palliative home care team, can be helpful in establishing an ethical care model in terminal cancer patients. [ 25 ] OOH is an integral part of our care process; provided in liaison with the LGP. In our study, 421 (83.20%) patients had access to the LGP.…”
Section: Discussionmentioning
confidence: 99%
“…Usually the FPs tend to "limit their services to and referral and were less likely to see patients and prescribe medicine, to provide phone follow-ups, to provide home visits or to offer bereavement care for the family" (28). Interestingly, a prior Taiwan study revealed low willingness of FPs to provide palliative home care (29).…”
Section: Discussionmentioning
confidence: 99%
“… 19 Home visits to cancer patients by general practitioners also allow for the choice of a home death. 20 This is an important step to respect the autonomy of those who desire to spend their last days at home.…”
Section: Discussionmentioning
confidence: 99%